2020
DOI: 10.1016/j.dib.2019.104918
|View full text |Cite
|
Sign up to set email alerts
|

Database of persistent organic pollutants in umbilical cord blood: Concentration of organochlorine pesticides, PCBs, BDEs and polycyclic aromatic hydrocarbons

Abstract: Persistent organic pollutants (POPs) have been banned over the last decades for being damaged to the environment and to the health of humans and animals. However, due to their lipophilic nature and resistance to degradation, they are frequently detected in biological samples. Its presence has been associated with the increased risk of suffering from different diseases in human series, being newborns and children especially sensitive. The present data reports umbilical cord blood levels of twenty organochlorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…In turn, Cabrera-Rodríguez et al (2020) reported the levels of PBDEs in a cohort from La Palma (Canary Islands). BDE-85 was not detected in any of the samples, while the levels of other congeners ranged between 0.006 to 0.078 ng/mL (36).…”
Section: Polybrominated Biphenyl Ethers (Pbdes)mentioning
confidence: 81%
“…In turn, Cabrera-Rodríguez et al (2020) reported the levels of PBDEs in a cohort from La Palma (Canary Islands). BDE-85 was not detected in any of the samples, while the levels of other congeners ranged between 0.006 to 0.078 ng/mL (36).…”
Section: Polybrominated Biphenyl Ethers (Pbdes)mentioning
confidence: 81%
“…Similarly, several flavonoids were known to possess antilarval activity against Aedes aegypti and their mechanisms were also understood 52 . Acenaphthene has been described as a pesticide belonging to the polycyclic aromatic hydrocarbon group of compounds 53,54 . This compound has been listed as the major compound with antilarval activity in the active fraction in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These new “essential elements” for industry are now being studied in terms of their toxicity, as it has been observed that their presence in living beings has been increasing in recent years [ 19 , 23 , 24 , 25 , 29 , 30 , 31 , 32 , 33 ]. Their toxic actions include cell damage, interference with enzymes, proteins and macromolecules, damage to cell organelles, and even carcinogenesis, according to available epidemiological and experimental studies [ 34 ].…”
Section: Introductionmentioning
confidence: 99%